Identificación de peces (Ictiofauna) del lago del Parque Metropolitano La Sabana realizado en el II Taxatón 2017, San José, Costa Rica (Repertorio Científico, 2024)
The II Taxathon (inventory and identification of organisms) in La Sabana lagoon conducted an identification inventory of ichthyofauna (fish species), which allowed the expansion of the biodiversity register that inhabits the site. The methodological basis consisted of carrying out a quick one-day inventory through catches with a catch net (drop net) launched from the lake shore from different points. After the catch, the fish were sheltered in an ice chest to record and identify the species and taxonomic family to which they belonged; in the end they were released back into the lagoon. The results achieved the capture of: 3 “Tiger Guapotes” (Parachromis managuensis), 3 “Mojarras” (Cichlidae), 1 “Olomina” (Alfaro cultratus), 1 Largemouth Bass (Micropterus salmoides), 1 Devilfish (Pterygoplichthys sp) and 39 “Tilapias” (Oreochromis sp). Oreochromis sp showed predominance due to the introduction of 200 fry in 2015 and due to the environmental characteristics of the lake as it is a shallow body of water and suitable for both Oreochromis sp and the other cichlids found (Mojarra and Guapote). The Cichlidae family obtained a greater presence than the other families. However, the presence of Micropterus salmoides and Pterygoplichthys sp are an important indicator of the introduction of invasive species to both artificial and natural ecosystems, since these are voracious freshwater fish species that have considerably affected native fish populations. It is recommended to carry out a deeper sampling to identify other types of species, increase the inventory of specimens by species and family. Registry that will provide more information on the current environmental status of La Sabana lagoon
Keywords: Peces, lago, inventario rápido, Cichlidae especies invasoras